IMPACT OF GENERAL RESOLUTION N° 90/2021 ON PRESIDENTE FRANCO'S MSMES - Gabriel Moral González, Alex; Javier Medina Alderete, Hugo; Elena Garay Vázquez, María; Báez Insfrán, Leticia (Revista Gênero e Interdisciplinaridade, 2023)
The objective of this work is to identify the impact of the new General Resolution No. 90/2021 on MSMEs in Presidente Franco, the proposal of this research is to publicize the impact of the new General Resolution No. 90/2021 and the importance it has for the future success of your business. The research developed in this work consists of four Units: Unit I: General Resolution 90/21 Unit II: SMEs. Unit III: Regulatory legal framework. The research was carried out with a quantitative and qualitative approach and a descriptive level of research. The survey was used as a data collection technique, in such a way that 15 entrepreneurs from the city of Pdte were selected for the sample. Frank. The results obtained showed that the majority of entrepreneurs do not have knowledge regarding the RG90, it is necessary to carry out training on this tax to provide better advice to taxpayers of this regime.